The Concept Of The Night And The Day In The Quran: A Comparative Interpretation Study - Barmawi, Mahral; Muhammad, Muhammad (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Night and day is a dualism of time that comes and goes in human life. God makes night and day with various virtues for humans so that they understand and live life well. However, the fact that some people do not work and use the time of the night and day correctly according to the Koran. Thus, this study aims to find out the concepts of al-layl and al-nah?r in the Koran, the efficiency and effectiveness of al-layl and al-nah?r as well as the wisdom of these two times in life. The methodology used is qualitative research with descriptive methods. The main source is in the form of the Koran al-karim by studying the verses of al-layl and al-nah?r. Data processing techniques carried out in three ways, namely: data reduction; collect and look for the core verses of al-layl and al-nah?r from the aspects studied, display data; systematically summarize the verses of al-layl and al-nah?r, verification of data; draw conclusions about al-layl and al-nah?r. The results obtained indicate that the work done at night is coercive and the work done during the day is a demand and a necessity. Thus, this shows that the night is a dark state and the day is a bright state. God makes the night to rest, sleep and calm down, and the day to work and try to find the necessities of life. Therefore, night and day for humans as a time to strike a balance between rest and activity, the momentum to carry out kindness and obedience, and to improve the quality of self through worship, work, and study The God verses.